Locational Choice and Spatial Wage Inequality - Felix Schran (Institute of Labor Economics (IZA), 2019)
During the last few decades, aggregate wage growth has been very unevenly distributed across space in Germany. While wages in Southern German local labor markets rose by up to 28 log points, they increased only modestly or even declined in the north. Similar results apply to employment changes. Overall, this has led to a strong positive correlation between local wage and employment growth. What is driving these differential trends across space? This paper examines to what extent regions with growing employment are increasingly paying workers higher wage premia or, in contrast, to what extent the quality of workers in growing regions has risen. To decouple the demand for skill and supply of skill from each other, I estimate how regional wage premia have changed over time using administrative panel data that allow me to hold constant changes in unobserved worker quality. I find that wage premia in regions with expanding employment did not rise more than in regions with declining employment. Instead, the quality of workers in growing regions went up. I investigate the importance of various possible observables for this relationship including local amenity differences, changes in occupation and industry structure as well as variation in education rates. Last, I explore the impact of changing wage premia and changing worker quality on the recent rise in the density wage premium.
Keywords: R11; R12; J21; J24; J31; 330; location choice; density premium; Roy model